Kappaphycus alvarezii supplementation attenuates blood pressure, blood cholesterol, ACE and antioxidant activities in hypertensive and hypercholesteroleamic rats - Mahadi, Mahani; Azizul, Mohamad Syahmi; Eshak, Zolkapli; Ibrahim, Aida Hamimi; Md Akim, Abdah; Kamal, Nurkhalida (Faculty of Medicine and Health Sciences, Universiti Putra Malaysia, 2021)
Introduction: Kappaphycus alvarezii (K. alvarezii) or locally known as red seaweed, was claimed to improve health and well-being. The goal of this study is to investigate how K. alvarezii affects blood pressure (BP), total cholesterol (TC), ACE, and antioxidant activities in rats with hyperten-sion and hypercholesterolemia (HTN-HC). Methods: Induction of HTN-HC was achieved by feeding rats a high sodium fat diet containing 1% cholesterol+7% sodium chloride (NaCl) for 6 weeks except for Normal group. HTN-HC rats were then supplemented with K. alvarezii (5 % (w/w) or 10% (w/w) per food intake) or treated with Captopril 30mg/kg/day + Simvastatin 2 mg/kg/day, or on similar diet for another 4 weeks. Before and after induction, as well as after treatment, BP and TC were measured. The rats’ TC, ACE, and antioxidant activities were analysed using blood and liver samples. Results: The results demonstrate that BP and TC were significantly higher in all groups except the Normal Control after the induction period (p<0.05). Drug-treated rats (statin and captopril) and K. al-varezii significantly lowered BP and TC levels when compared to the HTN-HC group (p<0.05). Compared to the drug-treated and K. alvarezii groups, the HTN-HC group had the highest ACE activity (p<0.05). Meanwhile, HTN-HC rats had the lowest FRAP value and the highest CAT activities, while 10% K. alvarezii had the opposite reading (p<0.05). Conclusion: In conclusion, K. alvarezii improves blood pressure and total cholesterol levels while decreasing ACE activity in HTN-HC induced rats.